OsARM1, an R2R3 MYB Transcription Factor, Is Involved in Regulation of the Response to Arsenic Stress in Rice - Wang, Feng-Zhu; Chen, Mo-Xian; Yu, Lu-Jun; Xie, Li-Juan; Yuan, Li-Bing; Qi, Hua; Xiao, Ming; Guo, Wuxiu; Chen, Zhe; Yi, Keke; Zhang, Jianhua; Qiu, Rongliang; et al. (Frontiers in Plant Science, 2017)
Bioaccumulation of arsenic (As) in rice (Oryza sativa) increases human exposure to this toxic, carcinogenic element. Recent studies identified several As transporters, but the regulation of these transporters remains unclear. Here, we show that the rice R2R3 MYB transcription factor OsARM1 (ARSENITE-RESPONSIVE MYB1) regulates As-associated transporters genes. Treatment with As(III) induced OsARM1 transcript accumulation and an OsARM1-GFP fusion localized to the nucleus. Histochemical analysis of OsARM1pro::GUS lines indicated that OsARM1 was expressed in the phloem of vascular bundles in basal and upper nodes. Knockout of OsARM1 (OsARM1-KO CRISPR/Cas9-generated mutants) improved tolerance to As(III) and overexpression of OsARM1 (OsARM1-OE lines) increased sensitivity to As(III). Measurement of As in As(III)-treated plants showed that under low As(III) conditions (2 μM), more As was transported from the roots to the shoots in OsARM1-KOs. By contrast, more As accumulated in the roots in OsARM1-OEs in response to high As(III) exposure (25 μM). In particular, the As(III) levels in node I were significantly higher in OsARM1-KOs, but significantly lower in OsARM1-OEs, compared to wild-type plants, implying that OsARM1 is important for the regulation of root-to-shoot translocation of As. Moreover, OsLsi1, OsLsi2, and OsLsi6, which encode key As transporters, were significantly downregulated in OsARM1-OEs and upregulated in OsARM1-KOs compared to wild type. Chromatin immunoprecipitation-quantitative PCR of OsARM1-OEs indicated that OsARM1 binds to the conserved MYB-binding sites in the promoters or genomic regions of OsLsi1, OsLsi2, and OsLsi6 in rice. Our findings suggest that the OsARM1 transcription factor has essential functions in regulating As uptake and root-to-shoot translocation in rice.